Visible light photocatalytic degradation of tetracycline using copper ferrite nanoparticles synthesized via Glycine-Assisted combustion method - A. Dinesh; K. Radhakrishnan; V. Renuga; Rajendra P. Patil; Suriyaprakash Rajadesingu; S. Suthakaran; L. Guganathan; Manikandan Ayyar; Madhappan Santhamoorthy; Lalitha Gnanasekaran; Munawar Iqbal (Results in Chemistry)
Copper Ferrite (CuFe2O4) nanoparticles (NPs) were synthesized by the combustion-assisted method using glycine as a fuel to evaluate their photocatalytic degradation efficiency for tetracycline (TC) under visible light. Several analytical methods were used to confirm the synthesized CuFe2O4 NPs. X-ray diffraction (XRD) was used to check the phase’s structure and purity, FT-IR was used to find out what functional groups were present, UV–Vis diffuse reflectance spectroscopy (DRS) was used to look at the optical properties, and scanning electron microscopy (SEM) was used to see the structure’s shape. These results confirm the formation of highly crystalline CuFe2O4 NPs. The photocatalytic degradation of TC was studied using visible light and the effect of parameters such as the concentration of the catalyst (0.5 g/L to 2.5 g/L), initial TC concentration (10– 50 mg/L) and irradiation time (30–150 min). The degradation efficiency reached a maximum value of 95.8 % for a 150 min irradiation under the optimum condition of the photocatalytic activity was further raised by 25 % by the addition of hydrogen peroxide (H2O2). The CuFe2O4 NPs had rather high recyclability after the photocatalytic process, they had 90 % of their initial activity, which was tested after the fifth run. This study shows that green synthesized CuFe2O4 NPs are potentially useful as reusable visible-light photocatalysts for breaking down drugs, specifically tetracycline, through oxidation in water.